Presentation for Tackling Obesity and Noncommunicable Diseases in Mexico: A Policy Approach - Barquera, Simón (2023)
Globally, the prevalence of overweight and obesity has nearly tripled since 1975—among adults over the age of 18, more than 1.25 billion are overweight and 650 million are obese. Overweight and obesity affects more than 340 million children and adolescents ages 5 to 19 and nearly 39 million children under 5. These rates have risen significantly in low- and middle-income countries, as rising poverty and inequity, urbanization, and climate and humanitarian crises limit access to healthy diets, especially for the poorest and most marginalized.